Psychometric properties of the Persian version of the Second Victim Experience and Support Instrument - Hamid Sharif‐Nia; Nasrin Hanifi (Nursing Open, 2023)
Abstract Aim This study was designed to characterize the psychometric properties of the Persian version of the Second Victim Experience and Support Instrument (P‐SVEST). Design This study was a methodological and cross‐sectional study. Methods The SVEST was back‐translated into Persian and 10 experts assessed its content validity. Construct validity was determined through exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) with a total of 754 critical care and emergency nurses. Results The results of exploratory factor analysis showed that the P‐SVEST had four factors. These four factors accounted for 51.67% of the total variance. Also, these factors were confirmed by confirmatory factor analysis (root mean square error of approximation = (90%. confidence interval) = 0.058 [0.045, 0.071], goodness‐of‐fit index = 0.932, comparative fit index = 0.956, non‐normal fit index = 0.918, incremental fit index = 0.957 and Tucker–Lewis index = 0.944). Coefficients of Cronbach's alpha, McDonald's omega, composite reliability and maximum reliability for all of the factors were >0.7, demonstrating satisfied internal consistency.